(untitled) (Academia Journal of Medicine, 2019)
Background: Most medical colleges in India traditionally use the Long Case Examination (LCE) in both formative and summative patterns of assessment in clinic. This age-old issue has been addressed over the years by the introduction of several modifications of the LCE such as OSCE and OSLER. OSCE, though attractive in its brevity and specificity of focus, falls short in terms of being comprehensive. This study was taken up to compare conventional LCE to OSCE and OSLER. Subjects and Methods: Final year MBBS students, posted to Department of General Medicine, HIMS, Hassan were studied for 5 months. Type of study: Prospective observational study Four examiners were selected for the formative assessment: Examiners 1 and 2 were asked to assess the students assigned to Group 1; Examiners 3 and 4 were asked to assess Group 2. The OSLER method concentrates on the following ten items: (1) pace and clarity of presentation, (2) communication process, (3) systematic approach, (4) Establishment of case facts, (5) systematic examination, (6) Examination technique, (7) Establishment of correct physical findings. Results: The mean time taken for the assessment in Group 1 was 28.22 minutes and the SD was 7.588. The mean time taken for the assessment in Group 2 was 17.09 minutes and the SD was 4.546. Conclusion: In our study, the students seem to prefer the time-tested long case examination and did score better marks with the conventional method than with OSLER.